Clinical aspects for survivin: a crucial molecule for targeting drug-resistant cancers. Issue 5 (May 2015) - Singh, Neha; Krishnakumar, Subramanian; Kanwar, Rupinder K.; Cheung, Chun Hei Antonio; Kanwar, Jagat R.
Highlights: Survivin as a crucial biomarker for drug-resistant cancers. The role of survivin helping proliferation and survival in cancer. Survivin and its relation to other drug-resistance markers in cancer. Gataparsen and other molecules in clinical trials targeting survivin. Abstract : Drug resistance is frequently found in cancer patients who have prolonged chemotherapeutic treatments. Overcoming this phenomenon to make therapy available to these patients is one of the most important features in developing effective cancer therapeutic strategies. Identification of drug resistance causative molecules is one of the most focused areas of cancer research today. Many molecules have been identified in conferring cancer cells the property of drug resistance, and various small molecule inhibitors have been developed to target these molecules to restore the sensitivity of different traditional chemotherapeutic agents, which are frequently found to exhibit reduced potency during prolonged treatment, in cancer patients. Survivin, a member of the inhibitor of apoptosis proteins (IAP) family, has been identified as one of the most crucial biomarkers in the recognition of drug resistance. Survivin is overexpressed in tumor cells, helping in its proliferation and survival, and its overexpression is positively correlated with poor prognosis for cancer patients. Targeted therapeutic measures to inhibit survivin in cancers, particularly drug-resistant tumors, are the recent focus of research for cancer treatment.